Implementasi Algoritma C.45 Pada Data Pengolahan Limbah Kelapa Sawit - Wahyu Sri Rejeki (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The problems faced at PT. PP. London Sumatra Indonesia Tbk, Bagerpang Palm Oil Mill, is that there are still errors in the grouping of the liquid waste which have a bad impact and cause environmental damage and disrupt activities around the company. One way to process the data is to apply or use data mining techniques. Where data mining is the process of analyzing large data into information to determine the pattern of the conclusions of the data being analyzed. The application of the C.45 algorithm which later will explore existing data and will form a decision tree, where this decision tree will later help the company to know the grouping and processing of the liquid waste so as not to have a bad impact on the surrounding company